ARTIFICIAL INTELLIGENCE - ADVANTAGES, RISKS AND POSSIBLE THREATS - Lieutenant-General (Ret.) Associate Professor Constantin MINCU, Ph.D. (Annals: Series on Military Sciences, 2023)
The author considers that the subject of this article can be of interest to IT&C specialists from all states and private entities, as well as (and especially) to the Romanian Armed Forces. A focus on the field of Artificial Intelligence (AI) would also be beneficial for the Romanian governors, as a basis for the foundation of future development policies in several areas of economic, education, health, defence sectors, etc. Anyone can access various sources of information on the field of AI by using an applied Google search, where one can find dozens of book titles and articles on the subject matter, documents designed by renowned specialists from around the world. A major difficulty is the multiplicity of sources of information, which could discourage those interested due to lack of time, given the current tasks they have to deal with. The article is only intended to open up the interest in a field with explosive development in the last few years and with complex predictions about the advantages of AI, some risks and possible threats, all of which being currently on the agenda of politicians, specialists and technology companies all over the world.